Ethnic group attachment as the main predictor to inculcate altruistic prosocial behavior among Malaysian Indigenous (Orang Asli) adolescents - Ma’rof, Aini Azeqa; Hamsan, Hanina Halimatusaadiah; Abdullah, Haslinda; Mohd Khir, Azlina (Human Resource Management Academic Research Society, 2021)
Studies suggest that the Orang Asli adolescents who feel attached to their ethnic group engage in more altruistic prosocial behaviors. However, the psychological mechanisms that account for this association are not clear. Drawing on social identity and self-categorization theories, this study examined the association between social attachments (i.e., parental attachment, school attachment, peer attachment, and ethnic group attachment) and kindness value on altruistic prosocial behavior. Assessed among 402 Orang Asli adolescents, result shows that there were positive significant relationships between parental attachment, ethnic group attachment and kindness value on altruistic prosocial behavior. Meanwhile, there was a negative significant relationship of peer attachment on altruistic prosocial behavior. Further analysis revealed that ethnic group attachment served as the strongest predictor in inculcating altruistic traits among the Malaysian Orang Asli. The theoretical and practical implications of these findings were addressed.